Excitatory neuron-prone prion propagation and excitatory neuronal loss in prion-infected mice - Temuulen Erdenebat; Yusuke Komatsu; Nozomi Uwamori; Misaki Tanaka; Takashi Hoshika; Takeshi Yamasaki; Ayano Shimakura; Akio Suzuki; Akio Suzuki; Toyotaka Sato; Toyotaka Sato; Motohiro Horiuchi; et al. (Frontiers in Molecular Neuroscience)
The accumulation of a disease-specific isoform of prion protein (PrPSc) and histopathological lesions, such as neuronal loss, are unevenly distributed in the brains of humans and animals affected with prion diseases. This distribution varies depending on the diseases and/or the combinations of prion strain and experimental animal. The brain region-dependent distribution of PrPSc and neuropathological lesions suggests a neuronal cell-type-dependent prion propagation and vulnerability to prion infection. However, the underlying mechanism is largely unknown. In this study, we provided evidence that the prion 22L strain propagates more efficiently in excitatory neurons than inhibitory neurons and that excitatory neurons in the thalamus are vulnerable to prion infection. PrPSc accumulation was less intense in the striatum, where GABAergic inhibitory neurons predominate, compared to the cerebral cortex and thalamus, where glutamatergic excitatory neurons are predominant, in mice intracerebrally or intraperitoneally inoculated with the 22L strain. PrPSc stains were observed along the needle track after stereotaxic injection into the striatum, whereas they were also observed away from the needle track in the thalamus. Consistent with inefficient prion propagation in the striatum, the 22L prion propagated more efficiently in glutamatergic neurons than GABAergic neurons in primary neuronal cultures. RNAscope in situ hybridization revealed a decrease in Vglut1- and Vglut2-expressing neurons in the ventral posterolateral nuclei of the thalamus in 22L strain-infected mice, whereas no decrease in Vgat-expressing neurons was observed in the adjacent reticular nucleus, mainly composed of Vgat-expressing interneurons. The excitatory neuron-prone prion propagation and excitatory neuronal loss in 22L strain-infected mice shed light on the neuropathological mechanism of prion diseases.